ANALYSIS AND EVALUATION OF POTENTIAL FODDER AREAS SUITABLE FOR ORGANIC PRODUCTION IN THE CENTRAL ECONOMIC ZONE OF THE REPUBLIC OF SAKHA (YAKUTIA) - Valentina V. Osipova; Nikolai E. Pavlov; Ivan I. Sleptsov; Marianna I. Petrova (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Recently, introducing organic farming in agriculture has become widespread throughout the world. In Yakutia, there are scientific developments on organobiological farming using legumes and on the use of effective microorganisms and vermiculture in growing crops. Analysis and synthesis of the research results,s as well as calculations for rational land use, for environmentally friendly production and for reproducing soil organic matter will be the key argument in deciding on the transition to biologized farming technologies in the areas of the Central Economic Zone of the Republic of Sakha (Yakutia) (hereinafter CEZ).